Young Generation's Understanding of Sustainable Tourism and Its Impact on Travel Behavior - Veronica (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
This research explores the understanding of young people regarding sustainable tourism and its impact on their travel behavior. Young people have great potential to promote sustainable tourism practices due to their high environmental awareness and access to information through the internet and social media. The research method used is descriptive quantitative, with questionnaires distributed to young people aged 18-35 in Indonesia. Data analysis measures their understanding of sustainable tourism and its impact on travel behavior, such as choosing environmentally friendly destinations and participating in responsible tourism activities. The results show that 76.90% of respondents agree that young people play an important role in promoting sustainable tourism, but only 68.80% indicate that this understanding directly influences their travel behavior. About 66.00% of respondents choose destinations that support sustainability, while 77.00% agree that understanding the impact of tourism influences their choices. Furthermore, 77.30% participate in responsible tourism activities. The research concludes that young people have a high awareness of sustainable tourism practices, but there is a need for increased education and access to information to strengthen the impact of their understanding on travel behavior. These results provide insights for stakeholders to design effective strategies for promoting sustainable tourism among young people.